The Right to Freedom of Expression of Athletes: Between Law and Sporting Regulations - Zahrastnik, Kristjan (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
In this article, the author examines the legal justification for excluding political, religious, and racial expression by athletes. The analysis is grounded in the standards developed by the European Court of Human Rights regarding permissible restrictions on the right to freedom of expression, as well as in the application of a structured test to assess whether interferences with that right are legally justified. The article further provides a case-based analysis of examples that have shaped the scope of athletes’ freedom of expression, offering insight into the sanctions imposed on athletes for expressive conduct. Particular attention is devoted to the distinction between prohibited and permissible forms of expression, both at sports venues and within the athlete’s private or personal sphere. The article concludes by critically questioning the legal sustainability of a blanket prohibition on ideological expression by athletes at sporting events.